ASSISTANCE TO ADOLESCENTS WHO USE PSYCHOACTIVE SUBSTANCES: ROLE OF THE PSYCHOSOCIAL CARE CENTER - Bruna Rios Paim; Daniele Dalla Porta; Diana Mara Sarzi; Mirela Frantz Cardinal; Daiana Foggiato de Siqueira; Amanda de Lemos Mello; Marlene Gomes Terra (Universidade Federal do Paraná, 2017)
The present study aimed to gain insight into the role of a Psychosocial Care Center for Users of Alcohol and other Drugs (CAPS AD) that assists adolescents who usepsychoactive substances, from the views of the professionals of Guardianship Councils and the Judiciary. Qualitative researchconductedfrom June to August 2015, in units of a Psychosocial Care Network (RAPS) for adolescents, in a city of the state of Rio Grande do Sul, based on semi-structured interviews with 13 professionals from Social Work and the Judiciary. Two categories emerged from data analysis: The role of the Psychosocial Care Center Alcohol and other Drugsand Challengesfaced bythe CAPS professionals regarding the delivery of care who use alcohol and other drugs.